Multivariate Analyses of Soil Properties and CO2 Emissions Under Long-Term Fertilization and Crop Rotation in Luvic Chernozem - Gergana Kuncheva; Galin Gynchev; Jonita Perfanova; Milena Kercheva; Lev Tribis; Hristo Valchovski (Nitrogen)
The key objectives of contemporary agriculture are restoring biodiversity, preserving ecosystem health, reducing the effects of climate change, and producing safe and healthy foods. Maintaining high soil fertility while reducing greenhouse gas emissions requires a precise assessment of how fertilization and crop rotation affect carbon and nutrient cycles in agroecosystems. Fertilization affects soil conditions, which alters the environment for soil microbial development and influences the number and composition of soil microbial communities, leading to changes in nutrient and carbon cycling. There is a lack of long-term experimental data on the impact of fertilizer treatments on soil CO2 emissions, soil microbial communities, and their interactions. The novelty of this study is that it identified the fertilization effects on soil carbon sequestration, soil properties, and microbial communities in the context of a long-term fertilizer experiment in Luvic Chernozem. The fertilization treatments that were continuously pplied for 64 years under a four-crop (wheat, barley, corn, and bean) rotation were nitrogen (N), phosphorus (P), potassium (K), NP, NK, PK, NPK, and control. The chemical and microbiological soil properties and soil CO2 emissions were monitored. The highest organic carbon content was observed under the NPK (1.42%) and NP (1.43%) treatments. N fertilizer application most significantly affected soil properties, including pH, electrical conductivity, and soil organic carbon content, altering the environment for soil microbial development and influencing the number and composition of soil microbial communities. On average, the field-measured soil C-CO2 emissions were the most intensive under NP (2.76 kg ha−1 h−1), NPK (2.83 kg ha−1 h−1), and PK (2.51 kg ha−1 day−1) treatments.